2012
DOI: 10.5267/j.msl.2012.04.011
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study to measure the impact of e-business on organizational performance with an emphasis on integrated production information

Abstract: During the past few decades, there have been different studies on e-business but there are limited numbers of works accomplished on measuring the impact of e-business on supply chain. Although e-business may not directly influence on organizational performance, it can have significant indirect impact on unifying customers and suppliers, which yields to a better performance of organizations. In this study, we perform an empirical study to measure the indirect impact of e-business on organizational performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The results of this paper have indicated that the e-business could substantially improve the performance of project based organizations. The results of this survey are consistent with the results earlier proposed by Meftahi et al (2012) and represented a positive correlation between implementation of e-business and organizational performance.…”
Section: Resultssupporting
confidence: 91%
“…The results of this paper have indicated that the e-business could substantially improve the performance of project based organizations. The results of this survey are consistent with the results earlier proposed by Meftahi et al (2012) and represented a positive correlation between implementation of e-business and organizational performance.…”
Section: Resultssupporting
confidence: 91%
“…They reported that organizational culture varies across hospitals and over time, and this variation was at least in part related to consistent and predictable ways with different organizational characteristics and routine measures of performance. Meftahi et al (2012) performed an empirical investigation to measure the indirect impact of e-business on organizational performance. The proposed study of this paper designs a questionnaire and distributes it among 40 professional experts in various industries in province of Ilam, Iran.…”
Section: Introductionmentioning
confidence: 99%